Scaling up the saving for change financing mechanism in Mali. Activity report - Guindo, Samuel; Traoré, Ousmane; Akpoffo, Marius; Dossou-Yovo E.R (2024)
This report examines the scaling up of the Saving for Change (SfC) financing mechanism in Mali under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project. The SfC mechanism empowers rural women by enhancing their access to finance and promoting the adoption of Climate-Smart Agriculture (CSA) technologies. By organizing women into savings clubs, the initiative has improved financial inclusion, enabling participants to pool savings, access loans, and invest in income-generating activities. In 2024, 15,100 women benefited from SfC leading to increased household income (USD 505/ha), net profit (USD 393/ha), and improved food consumption scores, reducing food insecurity among beneficiaries. This report highlights the critical role of SfC in empowering women, addressing financial and agricultural challenges, and fostering climate resilience. Key actionable recommendations are presented to guide the further expansion and institutionalization of the SfC mechanism in rural Mali.